Market monitoring in Rwanda’s rice sector: Insights from recent events - Warner, James; Mukamugema, Alice; Mutabazi, Egide; Benimana, Gilberthe Uwera (International Food Policy Research Institute, 2025)
Summary • While domestic rice production has risen 16% over the past five years, district level growth rates are varied and suggest strong growth in some districts but reductions in others. Leveraging higher growth area’s successes could be used to further expand production in declining growth districts. • Microeconomic data suggests that smallholder rice farmers have slightly larger than average landholdings, grow at lower elevations, and sell about twice the percentage of crop value when compared to typical smallholders. • A declining Tanzanian rice premium over the last five years (2019-2024) suggests a greater substitutability between Rwandan and Tanzanian rice but specific reasons for this trend are unclear and warrant further research. Overall, a 50 percent premium has been reduced to currently about 20 percent. • Following a dramatic price increase in 2022, a subsequent large decrease in Tanzanian wholesale rice prices may have undermined government price setting in August 2024. Domestic producer rice price setting has been based on costs of production but appears to not consider other factors, such as the effects of imported prices of direct substitutes. A price analysis reveals that Tanzanian wholesale prices, valued in USD, fell about 37 percent from October 2023 to August 2024, while Rwandan retail rice prices were down only 14 percent. This relative price decrease could have effectively squeezed Rwandan processors when faced with government determined local producer prices that constricted potential profitability against rapidly declining Tanzanian prices. • Research presented below indicates that Tanzanian wholesale prices have large, immediate impacts on rice prices in Rwanda, but Rwandan prices have little to no effect on either imported or wholesale Tanzanian rice prices. Therefore, dramatic changes of Tanzania wholesale prices have large effects on both retail Tanzanian and Rwandan rice prices in Rwanda. This unidirectional effect highlights the importance of monitoring domestic and important international prices and studying prices which could have potentially helped policymakers adjust to market dynamics more effectively and better inform target interventions. We recommend developing an improved market monitoring and forecasting unit to better incorporate the food systems approach promoted in PSTA 5.